1961
DOI: 10.1083/jcb.10.3.335
|View full text |Cite
|
Sign up to set email alerts
|

Electron Stains

Abstract: Chemical studies have been carried out on the interaction of DNA with uranyl salts. The effect of variations in pH, salt concentration, and structural integrity of the DNA on the stoichiometry of the salt-substrate complex have been investigated. At pH 3.5 DNA interacts with uranyl ions in low concentration yielding a substrate metal ion complex with a UO++/P mole ratio of about ~ and having a large association constant. At low pH's (about 2.3) the mole ratio decreases to about 1/~. Destruction of the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

1961
1961
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Similar results have been obtained independently by Beer (2, 3) using uranyl nitrate at pH 3.5. The contrast in his pictures apparently is lower, and from his chemical studies (Zobel and Beer,28,29) it can be assumed that the UO2:P ratio in his preparation is ~1:2, whereas according to the results of Huxley and Zubay (14), in our preparation, the ratio should be 1 : 1 or higher, if not too much of it is lost during the washing of the grids. Even though BIBLIOGRAPHY…”
Section: Figurementioning
confidence: 95%
See 2 more Smart Citations
“…Similar results have been obtained independently by Beer (2, 3) using uranyl nitrate at pH 3.5. The contrast in his pictures apparently is lower, and from his chemical studies (Zobel and Beer,28,29) it can be assumed that the UO2:P ratio in his preparation is ~1:2, whereas according to the results of Huxley and Zubay (14), in our preparation, the ratio should be 1 : 1 or higher, if not too much of it is lost during the washing of the grids. Even though BIBLIOGRAPHY…”
Section: Figurementioning
confidence: 95%
“…It has been shown that histone can take up at least one-fifth and serum albumin at least one-seventh of the amount of uranyl which DNA will take up under the same conditions (14,28). We assume that most of the "background staining" in our preparations can be attributed to this binding of heavy metals mainly by the carboxyl groups in the protein film.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…We have recently identified uranaffin-positive granules in the "stem cells" of the primitive nervous system of Hydra, indicating, perhaps, an even older existence. Since the basis of the staining of the uranaffin reaction is the binding of uranyl ions to the phosphate groups of nucleotides (ZOBEL and BEER, 1961), it is possible that the dense cores identified in coelenterate neurosecretory granules using this technique, could alternatively be large concentrations of polyphosphates. Biochemical assays or ultrastructural hydrolytic digestion experiments will be necessary to positively identify the stained component as ATP.…”
Section: Phylogeneticmentioning
confidence: 99%
“…Ultrastructural cytochemical data from our laboratory indicated that the neurosecretory granules found in the neuroendocrine "stem cells" (WESTFALL,1973) of Hydra (PAYNE and CROMEY, 1987) also contain nucleotides (or polyphosphates) based on the chemical specificity underlying the uranaffin reaction (ZOBEL and BEER, 1961). These cytochemical studies indicate that nucleotides were perhaps present in the neurosecretory granules of the neurons of the early coelenterates, which phylogenetically represent the simplest of nervous systems (i. e., nerve net).…”
mentioning
confidence: 99%